Maslahah 'Ammah: (A Comparative Study of The Concept Maslahah 'Ammah According To Nahdlatul Ulama And Ulama Mazdhahib Al-Arba'ah) - al-Muthahhiri; M. Hasbi Umar; Ramlah (The Islamic Education and Multiculturalism Foundation, 2023)
The second similarity in terms of principles includes, a) paying attention to the realization of general welfare and benefit (maslahah 'âmmah) the welfare of national development in the life of the nation and state, b) rejecting damage and taking virtue (benevolence). As for the difference, it is stated that